2023
DOI: 10.1001/jamapsychiatry.2023.0109
|View full text |Cite
|
Sign up to set email alerts
|

Association of Implementation of Postoverdose Outreach Programs With Subsequent Opioid Overdose Deaths Among Massachusetts Municipalities

Abstract: ImportanceNonfatal opioid overdose is the leading risk factor for subsequent fatal overdose and represents a critical opportunity to reduce future overdose and mortality. Postoverdose outreach programs emerged in Massachusetts beginning in 2013 with the main purpose of linking opioid overdose survivors to addiction treatment and harm reduction services.ObjectiveTo evaluate whether the implementation of postoverdose outreach programs among Massachusetts municipalities was associated with lower opioid fatality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We performed the ITS using Poisson regression with overdispersion adjustment through a scale parameter and used logtransformed land area (square miles) as an offset. 25 The modeling sequence followed 3 steps. Model 1 was an unadjusted base model.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the ITS using Poisson regression with overdispersion adjustment through a scale parameter and used logtransformed land area (square miles) as an offset. 25 The modeling sequence followed 3 steps. Model 1 was an unadjusted base model.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the larger study identified 157 post-overdose outreach programs that were operating in Massachusetts prior to July 2019. A detailed survey completed by 138 of these programs was used to characterize their components (e.g., team composition, outreach approach, services provided) [ 4 ] and to explore associations between the presence of these programs and subsequent reductions in opioid overdose deaths [ 6 ]. The qualitative aim of the larger study involved conducting semi-structured interviews with 38 post-overdose outreach team members at 11 of these programs to further explore patterns observed in the quantitative data related to the implementation of these programs [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…These programs provide a range of services including referral to and navigation of addiction treatment systems, recovery support, overdose prevention education and naloxone distribution, and support for families and social networks of overdose survivors [ 5 ]. Implementation of these programs has been associated with lower rates of fatal opioid overdose at the municipal level [ 6 ], but the operational pathways through which they operate is not well understood [ 7 ] – including critical questions concerning whether incorporating law enforcement officers into outreach activities increases overdose survivors’ risk of arrest and other adverse outcomes [ 8 12 ]. Independent of team composition and team members’ background and training, post-overdose outreach work can cause mental stress among team members due to their close interactions with overdose survivors and families who have recently experienced a life-threatening event [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…First responders ( firefighters, EMS providers, law enforcement (LE) officers) may represent an under-utilized resource for connecting high-risk patients to OUD treatment, as they are oftentimes the only providers who have contact with individuals following an overdose, particularly when patients decline transportation to an ED or live in an "opioid treatment desert" (Allen et al, 2021;Cao et al, 2019;Centers for Disease Control and Prevention National Center for Injury Prevention and Control, 2021;Hyder et al, 2021). Thus, programs that leverage first responders' access to patients to provide harm reduction and connection to recovery resources may increase the chances of long-term recovery after an overdose (Diriba & Whitlock, 2022;Langabeer et al, 2020;Wagner et al, 2019;Xuan et al, 2023). Preliminary reports suggest that mobile multidisciplinary teams are effective in providing proactive outreach and harm reduction to these patients; however, little is known about program design and outcomes (Bagley et al, 2019;Langabeer et al, 2020;Xuan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, programs that leverage first responders' access to patients to provide harm reduction and connection to recovery resources may increase the chances of long-term recovery after an overdose (Diriba & Whitlock, 2022;Langabeer et al, 2020;Wagner et al, 2019;Xuan et al, 2023). Preliminary reports suggest that mobile multidisciplinary teams are effective in providing proactive outreach and harm reduction to these patients; however, little is known about program design and outcomes (Bagley et al, 2019;Langabeer et al, 2020;Xuan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%